2012
DOI: 10.4103/2277-9175.100129
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of post-spinal hypotension using crystalloid, colloid and ephedrine with three different combinations: A double blind randomized study

Abstract: Background:The benefit of prophylactic combination therapy using crystalloid and colloid preload with ephedrine has not been cleared to prevent maternal hypotension after spinal anesthesia at cesarean delivery. This study evaluated the efficacy of three combinational methods to prevent hypotension following spinal anesthesia.Materials and Methods:In this prospective double blind trial, 150 candidates of elective cesarean delivery under spinal anesthesia were randomly allocated to three treatment groups; 1---Ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
0
12
0
2
Order By: Relevance
“…However, the use of crystalloid preload with ephedrine bolus was found to be more effective in reducing the incidence of hypotension. [ 21 ] Bhardwaj et al . compared bolus dose (E = 5 mg, M = 0.5 mg, P = 30 µg) followed by infusion (E = 2.5 mg/min, M = 0.25 mg/min, P = 15 µg/min) with ephedrine, metaraminol, phenylephrine, respectively, and observed maternal hemodynamics, umbilical blood gases, and complications.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of crystalloid preload with ephedrine bolus was found to be more effective in reducing the incidence of hypotension. [ 21 ] Bhardwaj et al . compared bolus dose (E = 5 mg, M = 0.5 mg, P = 30 µg) followed by infusion (E = 2.5 mg/min, M = 0.25 mg/min, P = 15 µg/min) with ephedrine, metaraminol, phenylephrine, respectively, and observed maternal hemodynamics, umbilical blood gases, and complications.…”
Section: Discussionmentioning
confidence: 99%
“…Hypotension is defined as a fall greater than 30% in baseline levels, and bradycardia is defined as a heart rate of less than 60 beats/min. The administration of a high volume of crystalloid solution, placement of the patient in the Trendelenburg position, and administration of intravenous ephedrine and atropine are used to reduce hypotension ( 18 ). In the present study, no significant hemodynamic disorders occurred in the unilateral spinal anesthesia group (Group S).…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 ] Moreover, other study showed that integration of precautionary methods would be necessary for reducing hypotension following spinal anesthesia for the elective cesarean section and they mentioned to giving preloading with ephedrine as the best method. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%